Probiotics for woman’s health focus on urogenital infections and reproductive outcomes - Shah, Phagun; Kumar, Pratap; Gupta, Mukesh; Gadam, Mohan; Ganla, Kedar; Kumar, Priti; Satija, Roshi; Kale, Ashish; Chandra, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Depletion in vaginal Lactobacilli colonization is associated with poor urogenital health and adverse pregnancy outcomes. Probiotic supplements containing lactobacilli, when administered in adequate amounts, increased vaginal and gut colonization of Lactobacilli, reduced the incidence of bacterial vaginosis and other urogenital infections. Probiotic Lactobacilli reduced preterm births and improved fertility rates in women following in vitro fertilization. Probiotics may also improve implantation rate and live-birth rate in women undergoing IVF. The purpose of this review was to critically analyse the available literature for synthesizing evidence on the use of probiotics and its effect on urogenital and reproductive health in women.